Morpho-phylogenetic evidence reveals novel hyphomycetous fungi on medicinal plants in Southwestern China - Hong-Zhi Du; Ning-Guo Liu; Na Wu; Ratchadawan Cheewangkoon; Jian-Kui Liu (Mycology)
During a survey of saprobic fungi on medicinal plants in Southwestern China, thirty-nine hyphomycetous collections belonging to Dictyosporiaceae, Melanommataceae, and Stachybotryaceae were identified, representing nineteen distinct species. These taxa were characterised and identified based on morphological and culture characteristics, coupled with phylogenetic analyses of combined sequences of calmodulin (cmdA), the internal transcribed spacer region of ribosomal DNA (ITS), nuclear large subunit ribosomal DNA (LSU), RNA polymerase second-largest subunit (rpb2), the translation elongation factor 1-alpha (tef1-α), and β-tubulin (tub2). Twelve novel species are described, including Camposporium alangii, C. polygoni, Dendryphiella verrucosispora, Jalapriya cheirospora, Memnoniella cnidiicola, M. guttulatispora, M. reniformis, M. reynoutriae, M. verrucosispora, Sirastachys aspidistrae, Sir. ellipsoidispora, and Striatibotrys biguttulatispora. Additionally, three new host records, M. alishanensis, Sir. castanedae, and Stachybotrys chartarum, and four new hosts and geographical records of M. ellipsoidea, M. pseudonilagirica, Str. rhabdospora, and Virgatospora echinofibrosa are reported. Memnoniella nilagirica is revised and synonymised under M. pseudonilagirica. Key morphological characteristics, hosts specificity, and distributional data of Memnoniella, Sirastachys, and Striatibotrys were summarised. This study provides comprehensive illustrations, descriptions, and notes for each new taxon and record, marking the first report of these species from medicinal plants.